Outside-hospital assistance for children and adolescents with type 1 diabetes mellitus - Vanelli, M.; Corchia, M.; Iovane, et al., B. (Acta Biomedica Atenei Parmensis, 2006)
Telephone care, Telemedicine, Home care and Diabetic Camps are the most useful ways for Paediatricians to transfer diabetic care outside the hospital. These provide children with diabetes and their parents with an effective and practical tool to solve directly arising therapeutic problems and improve their quality of care and life. The advantages for the National Health Care System could be macroscopic: according to some studies, the Telephone care service allows to save 85% of the hospitalisation costs for children with acute metabolic intercurrent illnesses-related derangements. Telemedicine service, based on telephone line relying on the internet technology, is a complementary tool to follow children and adolescents with diabetes in out-patient clinic. The rare experiences in this field report a reduction in insulin doses and an improvement of metabolic control and quality of life. The Home care service has to be performed by a nurse and has to be useful for patients and parents to organize the management of diabetes at home and to improve therapeutic adherence. Diabetic camps give the opportunity to children and adolescents with diabetes to verify, outside the family and under health professionals’ supervision, their ability to manage the disease, and to increase own self-esteem.